Reflections upon the Drift Away from Democracy in the United States - Palmer, Geoffrey (Victoria University of Wellington Law Review, 2022)
In this article Sir Geoffrey reflects on democracy in the context of the United States, with special attention to the events of recent years both in the United States and internationally. A drift away from democracy is noted and an agenda for reform of the United States system is advanced for the purpose of strengthening democracy in a country which is a role model for many others.